A qualitative study of bereaved relatives’ end of life experiences during the COVID-19 pandemic - Hanna, JR; Rapa, E; Dalton, LJ; Hughes, R; McGlinchey, T; Bennett, KM; Donnellan, WJ; Mason, SR; Mayland, CR (SAGE Publications, 2021)
Background: Meeting the needs of relatives when a family member is dying can help facilitate better psychological adjustment in their grief. However, end of life experiences for families are likely to have been deleteriously impacted by the COVID-19 crisis. Understanding how families’ needs can be met during a global pandemic will have current/future relevance for clinical practice and policy.